Development of Novel Thiol-ene Ligation Strategies for Thiosugar and Peptide Synthesis - MCSWEENEY, LAUREN (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2019)
This thesis, entitled ?Novel Thiol-ene Ligation Strategies for Thiosugar and Peptide Synthesis?, is composed of 6 Chapters. The first chapter gives an overview of the radical-mediated thiol-ene and thiol-yne addition reactions, including a brief outline of thiyl radicals, intra- and intermolecular addition and the applications of these reactions in chemistry, biochemistry and other areas of research. Chapter 1 also explores the area of peptide ligation, including solid phase peptide synthesis and the advances that have been made to this field since the emergence of Native Chemical Ligation. In this section, some alternative routes to ligated peptides are discussed; such as desulfurisation, auxiliary mediated ligation, kinetically controlled ligation and expressed protein ligation. Following this, S,N-acyl transfer, the formation of an amide from a thioester through acyl migration, is detailed. Aspects of this acyl migration such as applications in nature, synthetic applications, the reversibility of the shift and the importance of the size of the cyclic intermediate are all covered. Lastly, this Chapter deals with the topic of thioacids; their synthesis and applications in peptide and protein chemistry. This chapter concludes with a brief outline of the work described within this thesis. The first part of this work, presented Chapter 2, details the intramolecular thiol- yne cyclisation of arabinose derivatives; a novel route to thiosugars bearing both endo and exo alkenes. This work involves the ring opening of O-benzyl-protected arabinose and installation of both alkyne and free thiol at either end of the open chain sugar. The methodology for this process was previously carried out in the Scanlan lab on D- arabinose and this work focuses on the same principle utilising the L-arabinose derivative. The results, which vary greatly from D- to L-glycal, depict an interesting new methodology for thioglycal synthesis, centred on the intramolecular thiol-yne coupling reaction. The second part of this work comprises of Chapters 3 and 4 and investigates intermolecular thiol-ene addition of α-amino thioacids onto peptidyl alkenes. This novel methodology furnishes an isopeptide with a thioether linkage, which, following S,N- acyl transfer, leads to the formation of a native peptide bond. The entire route is intended to provide an alternative to Native Chemical Ligation and is referred to throughout this thesis as Thiol-ene Mediated Peptide Ligation and Elimination (TEMPLE). Chapter 3 describes the utilisation of radical-mediated thiol-ene coupling onto terminal alkene moieties attached to peptides through Ser/Thr esterification. Attempts to subsequently provide a native peptide linkage are thoroughly discussed in this section. Chapter 4 explores the utilisation of dehydroalanine for TEMPLE, employing both ionic and radical-mediated pathways to provide thioether-linked isopeptides. This part of the work aims to prepare the small protein GLP-1 via TEMPLE from small fragments synthesised by SPPS. Chapter 5 concludes the work presented in this thesis and gives a brief outline of future work possible for this project. Finally, Chapter 6 describes the experimental procedures employed for this work and the characterisation of the compounds synthesised within this thesis.
APPROVED